Penentuan Status Mutu Air Laut Menggunakan Metode Indeks Pencemaran di Perairan Bontang Kalimantan Timur - Khairunnisa, Nia; Mandang, Idris; Munir, Rahmiati (Geophysics Study Program, Faculty of Mathematics and Natural Sciences, Mulawarman University, 2024)
Bontang City is a coastal city in East Kalimantan, directly bordering the Makassar Strait, with numerous residential, industrial, and trade areas along its coastline. These activities can impact the decline in seawater quality in Bontang City's coastal waters. The decrease in seawater quality will diminish the usability, productivity, and capacity of aquatic resources, ultimately reducing the wealth of natural resources. The high human activity along Bontang's coast is feared to cause seawater pollution, affecting the management of seawater quality now and in the future. This research aims to determine the quality status of seawater in Bontang waters using the Pollution Index (IP) method. Water quality sampling took place in September 2021 at 8 research stations and was analyzed at Mulawarman University's Water Quality Laboratory. The results were then compared with seawater quality standards based on Government Regulation No. 22 of 2021. The research findings categorize the seawater quality status in Bontang waters using the Pollution Index (IP) method as lightly polluted at all observation stations, with a range of values 1 > IP > 5. Parameters contributing to this condition are PO4-P and DO that do not meet quality standards. Parameters in accordance with quality standards for marine and port tourism include temperature, salinity, pH, BOD5, NO3N, and NH3-N. The increase in parameters exceeding the maximum quality standards comes from natural sources and industrial waste from high community activities